Relationship Between Receiving Respectful Midwifery Care (RMC) and Satisfaction with Newborn Care Services - Munawaroh, Munawaroh; Syam, Heriza (Poltekkes Kemenkes Jakarta III, 2024)
ABSTRACT The midwife's positive attitude in providing midwifery services and fulfilling the patient's needs is felt as satisfaction by the patient. WHO introduced the framework of Respectful Midwifery Care (RMC) in 2014, which is dignified and respectful care to increase patient satisfaction. The objective is to determine the relationship between acceptance of Respectful Midwifery Care (RMC) and satisfaction with newborn care. The population of this research is postpartum 1-40 days mothers who go through a normal delivery process with a normal baby. The researcher used purposive sampling with 102 respondents—furthermore. The data analysis used univariate and bivariate. Bivariate analysis will use Chi-Square tests. The research results showed that the most respondents were 92.2% of reproductive age, 92.2% had higher education, and 58.8% were unemployed. The researcher obtained a P value of .001 and OR 11.071 based on statistical tests. In conclusion, there is a relationship between RMC and the quality of services for newborn babies; it was proven by the respondents who received RMC 11 times that they were more satisfied than respondents who did not receive RMC.